Neuronal pathfinding and recognition: roles of cell adhesion molecules. - Chiba, A.; Keshishian, H. (Developmental Biology, 1996)
Neurons contact their neighbors through a diverse array of cell adhesion and other surface molecules. These molecules can exhibit highly regulated patterns of expression, underscoring their multiple roles in establishing specific interactions between neurons and their environment. Recent studies are beginning to ask how these membrane-bound neural recognition molecules interact with each other and intracellular signaling pathways within an individual neuronal growth cone, and direct the formation of neural connections during development.